2015
DOI: 10.2989/16085906.2015.1016987
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related stigma: implications for symptoms of anxiety and depression among Malawian women

Abstract: An estimated 11% of the adult population in Malawi, Africa, is living with HIV/AIDS. The disease has taken a toll on communities, resulting in high morbidity and mortality. Malawian women carry the burden of being caretakers for individuals infected with HIV while also worrying about their own health; however, little is known about how HIV/AIDS affects psychological functioning among Malawian women in areas hit hardest by the epidemic. To that end, this paper examined the influence of HIV-related stigma on sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
4
36
0
3
Order By: Relevance
“…[2425262728293031] Our study, however, interestingly found that stigmatization or discrimination toward HIV/AIDs carriers was low. HCPs’ attitudes were characterized by empathy and compassion.…”
Section: Discussionmentioning
confidence: 61%
“…[2425262728293031] Our study, however, interestingly found that stigmatization or discrimination toward HIV/AIDs carriers was low. HCPs’ attitudes were characterized by empathy and compassion.…”
Section: Discussionmentioning
confidence: 61%
“…HIV-related stigma continues to be a problem in the US (Ojikutu, Nnaji, Sithole-Berk, Bogart, & Gona, 2014; Shacham, Rosenburg, Onen, Donovan, & Overton, 2015) and has been shown to be associated with anxiety and depression (Kamen et al, 2015; Shacham et al, 2015). People living with HIV also exhibit levels of HIV-related stigma (Mannheimer et al, 2014), which may be related to affect, behavior and well-being among people living with HIV (Earnshaw, Smith, Chaudoir, Amico, & Copenhaver, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Third, women’s stigma related to HIV and PND cut across all of their identities mentioned above (31,32). Most prior work focuses on HIV-related stigma specifically and finds that women reporting greater stigma related to HIV in Malawi are significantly more likely to report depression (32). This indicates that in addition to women having an unexpected HIV diagnosis, HIV may contribute to PND through stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, literature suggesting that HIV and depression care should be combined in treatment and that providers should attend to the emotional and psychological needs of women need to be transferred to the perinatal population and expand beyond ART counseling (28,32). Additionally, examples exist that address PND at the community level using pre-existing primary care structures and training lay health workers in counseling (3638).…”
Section: Discussionmentioning
confidence: 99%